Production cross-sections for the residual radionuclides from the (nat)Cd(p,x) nuclear processes - Khandaker, Mayeen Uddin; Lee, Y.O.; Cho, Y.S.; Kim, G.N.; Kim, K.S.; Lee, M.W.; Kim, K. (Elsevier, 2008)
We measured the production cross-sections of the (107,111m,115g)Cd, (108m,108g,109g,110m,110,111g,1 13m,114m,115m,116m)In and (104g,105g,106m,110m,111g,113g)Ag radionuclides for proton-induced reactions on cadmium by using a stacked-foil activation technique in the energy rangy between 3 and 40 MeV at the MC-50 cyclotron of the Korea Institute of Radiological and Medical Science. The measured cross-sections were compared with the available literature data and the theoretical calculations by the model codes TALYS and ALICE-IPPE. The integral yields for thick targets were also obtained from the measured cross-sections of the produced radionuclides. The measured cross-sections, especially the indium (In) radionuclides have a significance for various practical applications: thin layer activation analysis, nuclear medicine, nuclear technology, radioactive waste handling, etc. (C) 2008 Elsevier B.V. All rights reserved.